New phases Bi12.5Ln1.5ReO24.5: Thermodynamics and influence of dopant size on lattice energy (Ln – lanthanide). (December 2015) - Matskevich, N.I.; Wolf, Th.; Greaves, C.; Adelmann, P.; Vyazovkin, I.V.; Matskevich, M.Yu.
Highlights: We synthesized new compound Bi12.5 Yb1.5 ReO24.5 . We measured formation enthalpies of Bi12.5 Yb1.5 ReO24.5 and Bi14 ReO24.5 . Bi12.5 Ln1.5 ReO24.5 lattice energies dependence on rare-earth reverse radii was done. Abstract: On the basis of experimental data the lattice energies for the new compounds Bi12.5 Ln1.5 ReO24.5 have been calculated using a Born–Haber cycle. It has been discovered that there is a linear dependence between lattice energies and inverse radii of lanthanide ions. It has been established that calculated and experimental lattice energies for Bi12.5 Yb1.5 ReO24.5 are in a good agreement. For the first time the compound Bi12.5 Yb1.5 ReO24.5 has been synthesized, its lattice parameters have been determined and its thermochemical characteristics have been measured. The determined unit cell parameters of Bi12.5 Yb1.5 ReO24.5 suggest that the structure is of cubic type, space group Fm3m, a = 0.55590(6) nm.